Analisis Pengendalian Kualitas Produk Sinter Ore dengan Metode Failure Mode And Effect Analysis (FMEA - Dwi Cahyono; Sahrupi Sahrupi; Ahmad Nalhadi (Jurnal INTECH Teknik Industri Universitas Serang Raya, 2017)
The problem that occurs in the production of sintered ore is the number of defective products. In this study it was conducted with the aim of knowing the factors that cause the product to become broken, understanding the processes that most often appear following the elements and providing proposed improvements to improve product quality and reduce them using the method of failure mode and effect analysis and seven tools. Based on the results of the highest Risk Priority Number (RPN) is the proportioning process with a score (252), Sintering with a score (168), Drum Mixing 2 with a score of 126, drum mixing 1 with a dozen (90), sintered cooling with a rating (45), and a sinter crusher with a score (18). The priority for repairs is the proportioning process.